Left Ventricular Dissecting Hematoma Caused by Tissue Stabilizer - Pasarad,Ashwini Kumar (2020)
Abstract Coronary artery bypass grafting is a commonly performed procedure for coronary revascularization. We describe the successful management of left ventricular dissecting hematoma, caused by the tissue stabilizer, while performing off-pump coronary artery bypass graft procedure.